Guru Sebagai Penyelidik : Faktor-Faktor Yang Mempengaruhi Kekerapan Aktiviti Kajian Tindakan Di Sekolah - Lee, Soon Guan (1997)
Action Research, a proven research methodology in the field of education, is still a new research topic in Malaysia. The purpose of this research project is to determine factors affecting the frequency of action research carried out in schools. The purposive sample for this research is a group of 32 teachers from throughout the state of Kedah; who have attended the 1996 Action Research Course, organized by the State’s Educational Resource Centre (SERC). This group of teachers' who have successfully completed at least one action research project are known as Action Researcher. Questionnaire for this survey is designed to measure the current status of Action Researcher in the following aspects: perception on Action Research, skills in carrying out Action Research, school climate condusiveness, and personal constraint. These factors are then correlated to the number of Action Research projects undertaken by each respondent. Results show that only skills factor has a positive correlation with the number of Action Research projects undertaken. Demographic comparison reveals that the most active Action Researcher are from secondary school, especially graduate teachers. Taking into account the conclusion derived from open-ended questions; this research project has come out with some recommendations to the relevant authorities, especially SERC on ways to realize the “Teacher As Researcher” movement.